Investigation of young children’s metacognitive and self-regulatory abilities in mathematics activities - Adagideli, Fahretdin Hasan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2013., 2013)
The aim of this study is to investigate metacognitive and self-regulatory abilities of young children at the age of 4 and 5 in mathematics activities. Meanwhile, another aim is to understand interactions of these abilities of young children with their mathematical skills and pedagogical context that support these abilities of young children. The observational method to display metacognitive and self-regulatory abilities of young children provides opportunities to observe children in a naturalistic manner. Moreover, it helps to collect evidence of these skills during children’s mathematics activities which are meaningful for children. 16 children from 4 year old group and 17 children from 5 year old group participate in this study. The findings show that young children exhibit metacognitive knowledge of persons (i. e. self, other), tasks and strategies; and metacognitive regulation (i. e. planning, monitoring, control and evaluation). Besides, the interaction between metacognitive and self-regulatory abilities of young children and their mathematical skills is identified. Moreover, the pedagogical context where children are supported emotionally, they are challenged in cognitive activities, they are provided with opportunities of feeling of control and of articulating their thinking is pointed out as the important factors to support these abilities of young children.
Keywords: Metacognition in children.; Self-control in children.; Mathematics -- Study and teaching (Preschool)